Sistem Informasi Geografis Pemetaan Daerah Rawan Bencana Alam Di Kabupaten Purbalingga Tahun 2021 - Anggi Ade Kurniawan; Bambang Herlambang; Ahmad Khoirul Anam (JURNAL ILMIAH RESEARCH STUDENT, 2024)
The Purbalingga Regency area has potential natural disaster risks that need to be identified and managed effectively. This research focuses on developing a Geographic Information System (GIS) to map areas prone to natural disasters in Purbalingga Regency. The main objective of this research is to provide reliable tools for related parties to understand, manage, and respond to potential natural disaster risks more efficiently. The research methodology involves the stages of spatial data analysis, natural disaster data collection, and integration of GIS technology. Thematic maps covering various types of natural disasters such as fires, landslides, and hurricanes were developed by considering topographic factors, rainfall, and disaster history. In addition, this map is equipped with detailed information such as the location of evacuation sites, evacuation routes, and other critical facilities. This system is implemented as a web-based application that can be accessed by authorities, disaster management agencies, and the general public. This application allows users to explore interactive maps, access disaster-related information, and facilitate disaster mitigation planning. With the GIS mapping of areas prone to natural disasters, it is hoped that Purbalingga Regency can increase preparedness and response to potential natural disasters, involve active community participation in mitigation efforts, and reduce the impact caused by natural disasters in the future